If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2-x)-(x+2)=55+9(x-3)
We move all terms to the left:
3(2-x)-(x+2)-(55+9(x-3))=0
We add all the numbers together, and all the variables
3(-1x+2)-(x+2)-(55+9(x-3))=0
We multiply parentheses
-3x-(x+2)-(55+9(x-3))+6=0
We get rid of parentheses
-3x-x-(55+9(x-3))-2+6=0
We calculate terms in parentheses: -(55+9(x-3)), so:We add all the numbers together, and all the variables
55+9(x-3)
determiningTheFunctionDomain 9(x-3)+55
We multiply parentheses
9x-27+55
We add all the numbers together, and all the variables
9x+28
Back to the equation:
-(9x+28)
-4x-(9x+28)+4=0
We get rid of parentheses
-4x-9x-28+4=0
We add all the numbers together, and all the variables
-13x-24=0
We move all terms containing x to the left, all other terms to the right
-13x=24
x=24/-13
x=-1+11/13
| -8n-4=-4n+4 | | 4x=123/4 | | 63+x=92 | | x-93=71 | | 0.40x=x-178 | | x+50=97 | | x+50=-90 | | 125+9c=30c | | -16+a=23 | | 0=0.6x+x | | f-24=156 | | 175+50n=150n | | -1/9a=12 | | 0.04(2c-50)=-0.8(c-3) | | -3.7=-1/8d | | -2.7=1/4x | | X=4y-13 | | -50=2(5–3y) | | 1/3t=-6.1 | | 2.3(y-1)=11.4(y-10) | | 12=0.50x+5 | | (3x+3)°=129 | | y-3/4=0 | | 7x-7=110° | | 12f-16=20 | | -3+9h=6 | | -3x-9=-10x-4x+2 | | 3a=24/a= | | (y-3)6y=4.5 | | -7=-13+x | | 0.67b+5=20−b | | 3x+12+9x=72 |